(untitled) (Research, Society and Development, 2020)
This work aims to characterize SESAI - MA organizationally and administratively, its territory and the insertion of its multidisciplinary teams to better understand the process of permanent education. Permanent education in Brazil has been developed as an ethical-political-pedagogical process that, in a simpler way, is to improve the quality of service provided by improving the theoretical and practical knowledge of its workers applied specifically to their work realities. In the context of Permanent Health Education for indigenous workers, it is of fundamental importance that these pillars that conceptualize the educational process are guiding the development of Permanent Health Education strategies offered to SESAI indigenous workers. The research was carried out through a questionnaire and interview with semi-structured questions applied to indigenous people in the village and to non-indigenous nursing technicians, target audience of permanent education activities carried out by SESAI (Special Secretary for Indigenous Health), regarding the respect for the characteristics of the axes of permanent education in health. In the work it was verified that the DSEI (Special Sanitary District of Maranhão) is concerned with the knowledge of its staff, both white and Indian, and that SESAI respects the ethnic specificities of the indigenous people, certain that it needs to make further progress in this regard. The understanding of continuing education in this research is very interesting, as knowing about the respect for the ethnic specificities of indigenous workers is extremely important for different peoples.